Investigating Factors that Influence Compliance of Digital Financial Service Agents to Legislation and Standards in Kenya - Njuguna, Rebecca Wanjiku (Department of Information Systems, 2021)
This study investigated the factors that influence compliance with existing legislation and standards among digital financial services (DFS) agents in Kenya. DFS in Kenya serve 60% of the adult population with at least 16 million subscribers. Much of these are attributable to the mobile money service Mpesa which accounts for the largest DFS market share. The number of DFS agents serving the market has grown to over five times the number of bank branches and ATMs in the country. With this growth in DFS, there have been many operational challenges among agents and the legislation has been at nascent. The aim of the study was to understand agent operational factors and how they influence compliance. Therefore, the main research question that guided the study was “How do operational factors affect compliance of DFS agents with agency banking legislation and standards in Kenya?” Additionally, the study investigated the compliance status among agents and identifiable groupings by compliance behaviour. Previous studies on DFS agents have identified persistent operational challenges but there has been no inquiry on how existing legislation addresses these challenges and whether their persistence is due to non-compliance. To investigate compliance, first, Configuration Theory (CT) was used to conceptualise DFS agents as organisations, classifying their operations under CT's principles of structure, strategy and environment. Subsequently, a conceptual model was developed with structure, strategy and environment as independent variables and compliance as the dependent variable. The first three propositions derived stated that structure, strategy and environment have an influence on compliance. The fourth proposition posed was that strategy has a greater influence on compliance than structure and environment. Quantitative paper-based questionnaires were used to collect cross-sectional data from 450 DFS agents in Kenya. A Partial Least Squares approach to Structural Equation Modelling (PLS-SEM) was applied to analyse the data on Smart PLS3. All four propositions were confirmed. Structure, strategy and environment had highly significant effects on compliance and strategy had the strongest effect on compliance. The findings suggest that Strategy, which was measured using training and technology utilization questionnaire items plays the biggest role in an agent's operations and compliance. Training equips agents with skills to manage liquidity, offer quality customer service, perform Know-Your-Customer (KYC), CustomerDue-Diligence (CDD) and suspicious transaction reporting (STR) procedures to assist with fraud detection and anti-money-laundering (AML) by identifying counterfeit customer identification documents, cash, and suspicious behaviour. Technologies such as CCTV cameras, counterfeit cash detectors and cash counting machines not only enhance efficiency but support the enforcement of the fraud and AML procedures. A two-step cluster analysis was performed to classify agents by compliance behaviour. Two distinct clusters emerged. The cluster where majority of agents fell exhibited better training and awareness of existing legislation, higher education levels and financial resources and was compliant with most of the questionnaire items measured. The second cluster with fewer agents was uncompliant on most questionnaire items measured and was characterised by lower education levels, financial resources and training levels. There were commonalities in both clusters which were relatively low scores on legislation awareness, and low compliance scores on liquidity and possession of DFS agent operational manuals. These findings suggest that an agent with a good alignment of financial and human resources (structure), good training and technology (strategy) and well informed about existing legislation (environment) would be compliant and is likely to experience less operational challenges. The findings also provide insights on what areas agents can take initiative for their own development, the most important being liquidity management, technology optimization and educating themselves on what legislations apply to them, and their compliance roles and responsibilities. Lastly, the study provides regulators with exploratory findings on the state of compliance among DFS agents in Kenya, indicating which areas agents are having most difficulty with. Banks and MNOs must recognize the crucial role of training and tailor programs to be responsive to all agent's operational and legislative areas.